Vertically implanting MoSe2 nanosheets on the RGO sheets towards excellent multi-band microwave absorption. (September 2022) - Fu, Xiao-Ying; Zheng, Qi; Li, Lin; Cao, Mao-Sheng
Abstract: It is still a challenging project for developing electromagnetic (EM) wave absorption materials with the properties of multi-band absorption in the field of microwave absorption. Herein, honeycomb-like MoSe2 @reduced graphene oxide (RGO) composites are successfully constructed by a facile one-step solvothermal method. The polarization and conductive loss can be precisely tailored by vertically implanting MoSe2 nanosheets on the RGO sheet. It is notable that three-band absorption, including S, X, and Ku bands, was achieved in the composites. The optimized MoSe2 @RGO composite exhibits excellent microwave absorption performance, the maximum reflection loss (RL) value can reach −56.9 dB and an effective absorption bandwidth (EAB) value can reach 4.12 GHz. The excellent microwave attenuation capability is attributed to the synergy effect of conductive loss, multiple relaxations, and excellent impedance matching in the composites. Therefore, this work provides a new paradigm for developing efficient multifunctional EM wave absorbers. Graphical abstract: Image 1 Highlights: The growth mechanism of MoSe2 @RGO composites by vertically implanting MoSe2 nanosheets distributed on RGO was clarified. The tunable electromagnetic properties were revealed. Multi-band microwave absorption with S, C, and Ku bands was realized. The multiple EM loss mechanisms in the composite were discussed in detail.